Trail log - 1995-1997 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 1995)
Rolston accounts: Africa: East Africa, South Africa, 1995, Slovenia, 1995. Yellowstone wolves. Minnesota wolves. Sweden, Oxford, Denmark, Romania, Estonia, 1996. Australia, 1996. Siberia, Lake Baikal, 1997.